ANALISIS MEDIA PEMBELAJARAN INTERAKTIF BERBASIS DIGITAL DI SEKOLAH DASAR STUDI LITERATUR SISTEMATIS - Evika Widya Puspita; Putri Yanuarita Sutikno; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the types, effectiveness, as well as the advantages and limitations of digital-based interactive learning media in elementary schools. The method employed is a Systematic Literature Review (SLR) using the PRISMA approach, which includes the stages of identification, screening, eligibility, and inclusion. Data were collected using the Publish or Perish application from Google Scholar and Crossref databases, with a publication range from 2022 to 2026, resulting in 25 relevant articles for analysis. The findings indicate that interactive learning media consist of audio, audiovisual, and digital interactive media such as videos, multimedia, educational games, and web-based applications. These media have been proven effective in improving students’ learning outcomes across cognitive, affective, and psychomotor domains, as well as enhancing students’ motivation, interest, and engagement in the learning process. However, their implementation still faces challenges, including limited facilities, technological access, and teachers’ competencies. Therefore, optimizing the use of interactive learning media is necessary to support more effective and innovative learning.